The Relationship of Sweet Potato Germplasm Based on Morphological Characters - Rahajeng, Wiwit; Restuono, Joko; Indriani, Febria C. (Jurnal Biodjati, 2023)
Information about the morphological and genetic characteristics of sweet potato (Ipomoea batatas) is important in the variety development program. This experiment aimed to determine the diversity and genetic relationship of sweet potato accessions from NTT based on morphological character data. The research was carried out at Kendalpayak Research Station, Malang, East JavaÂ  from April - September 2019. The materials used were seventy-one sweet potato germplasm from the ILETRI collection (collected from NTT). Each accession was planted on a 1 m Ã— 5 m plot size, with a spacing of 100 Ã— 20 cm (single row). Fertilization was carried out using a dose of â€œ100 kg urea + 100 kg SP36 + 200 kg KCl ha-1â€. The observed characters were the vines length, growth type, internode length, leaf length, leaf width, leaf size, leaf bone color, leaf shape, leaf characteristics, lobes number, lobe shape, mature leaf color, shoot color, pigmentation of petiole, young stems pigmentation (dominant and secondary color), young leaves feathers, tuber skin color, tuber flesh color, weight of canopy, number of tubers perplot, weight of tubers perplot, number and weight of tubers perplot. Cluster analysis was carried out using the Minitab 17 program. There was morphological diversity in seventy-one accessions of sweet potato germplasm from NTT. Principal component analysis resulted in seven main components with the proportion of diversity 76.3%. cluster analysis, seventy-one accessions of sweet potato germplasm were divided into fifteen accession groups on the basis of 80% degree. Characteristics of shoot color, mature leaf color, leaf size, petiole pigmentation, and leaf bone color contributed greatly to the total diversity.